Quantifying the influence of climate and biological drivers on the interannual variability of carbon exchanges in European forests through process-based modelling - DELPIERRE, N.; SOUDANI, K.; François, C.; Le Maire, G.; BERNHOFER, C.; Kutsch, W.; Misson, L.; Rambal, S.; Vesala, T.; Dufrêne, E. (Agricultural and Forest Meteorology, 2012)
It is necessary to increase our understanding of the inﬂuence of climate and biological drivers on the interannual variations in carbon (C) exchange between forests and the atmosphere. To this aim, a processbasedmodel(CASTANEA) was used for simulating C exchanges over four European forests, encompassing a broad latitudinal gradient (from Mediterranean to boreal climate zones), for the years 2000–2007. CASTANEA reproduced 74–95% of the daily and 35–84% of the annual variance in daytime net ecosystem productivity (NEP). Constrained simulations allowed us to isolate the individual contributions of climatic drivers (radiation, temperature and relative humidity), hydrological drivers (soil water) and biological drivers (canopy dynamics, the thermal acclimation of photosynthetic capacities in evergreens, and vegetative and microbial C pools) to the anomalies in C exchange for timescales ranging from daily to annual. Orthonormal wavelet transformation of these single-contribution time series allowed us to quantify the individual drivers’ inﬂuences on ﬂux variance across time scales. High frequency departures from mean annual C exchange patterns were mostly caused by hydroclimate modulations (87–99% of the ﬂux variance from daily to weekly scales). The integration of these anomalies at the annual scale yielded a higher contribution of biological drivers: we identiﬁed a primary controller of gross primary production (GPP) variations through modulations of soil water in both the Mediterranean Quercus ilex and the temperate Fagus sylvatica forests; we also identiﬁed at the annual scale a complex determinism for both coniferous sites, with an unexpectedly higher contribution of the thermal acclimation driver at the temperate (warmer) site. Although all but one site experienced structural perturbations during the study period, interannual variations in ecosystem respiration (Reco) were readily related to changes in temperature and soil water, with a low contribution from variations in C pools at the annual scale. As a result of the preponderant dependence of net ecosystem production (NEP) on GPP ﬂuxes, the inferred determinism of simulated net exchanges appeared similar to that of GPP. However, compensations occurred, leading, for example, to a much lower inﬂuence of soil water modulations on NEP than on GPP or Reco at the Mediterranean site.
Keywords: Carbon exchanges; Climate drivers; Ecosystem functional properties; European forests; Interannual variability; process-based model

Exceptional carbon uptake in European forests during the warm spring of 2007: a data–model analysis - DELPIERRE, N.; SOUDANI, K.; François, C.; Köstner, B.; Pontailler, J.-Y.; NIKINMAA, E.; Misson, L.; Aubinet, M.; BERNHOFER, C.; Granier, A.; GRÜNWALD, T.; HEINESCH, B.; et al. (Global Change Biology, 2009)
Temperate and boreal forests undergo drastic functional changes in the springtime, shifting within a few weeks from net carbon (C) sources to net C sinks. Most of these changes are mediated by temperature. The autumn 2006–winter 2007 record warm period was followed by an exceptionally warm spring in Europe, making spring 2007 a good candidate for advances in the onset of the photosynthetically active period. An analysis of a decade of eddy covariance data from six European forests stands, which encompass a wide range of functional types (broadleaf evergreen, broadleaf deciduous, needleleaf evergreen) and a wide latitudinal band (from 44° to 62°N), revealed exceptional fluxes during spring 2007. Gross primary productivity (GPP) of spring 2007 was the maximum recorded in the decade examined for all sites but a Mediterranean evergreen forest (with a +40 to +130 gC m−2 anomaly compared with the decadal mean over the January–May period). Total ecosystem respiration (TER) was also promoted during spring 2007, though less anomalous than GPP (with a +17 to +93 gC m−2 anomaly over 5 months), leading to higher net uptake than the long-term mean at all sites (+12 to +79 gC m−2 anomaly over 5 months). A correlative analysis relating springtime C fluxes to simple phenological indices suggested spring C uptake and temperatures to be related. The CASTANEA process-based model was used to disentangle the seasonality of climatic drivers (incoming radiation, air and soil temperatures) and biological drivers (canopy dynamics, thermal acclimation of photosynthesis to low temperatures) on spring C fluxes along the latitudinal gradient. A sensitivity analysis of model simulations evidenced the roles of (i) an exceptional early budburst combined with elevated air temperature in deciduous sites, and (ii) an early relief of winter thermal acclimation in coniferous sites for the promotion of 2007 spring assimilation.
Keywords: 13 october 2008; august 2008 and accepted; European forests; functional drivers; net carbon uptake; process-based model; received 30 may 2008; revised version received 30; spring

Exceptional carbon uptake in European forests during the warm spring of 2007: a data–model analysis - DELPIERRE, N.; SOUDANI, K.; François, C.; Köstner, B.; Pontailler, J.-Y.; NIKINMAA, E.; Misson, L.; Aubinet, M.; BERNHOFER, C.; GRANIER, a; GRÜNWALD, T.; HEINESCH, B.; et al. (Global Change Biology, 2009)
Temperate and boreal forests undergo drastic functional changes in the springtime, shifting within a few weeks from net carbon (C) sources to net C sinks. Most of these changes are mediated by temperature. The autumn 2006–winter 2007 record warm period was followed by an exceptionally warm spring in Europe, making spring 2007 a good candidate for advances in the onset of the photosynthetically active period. An analysis of a decade of eddy covariance data from six European forests stands, which encompass a wide range of functional types (broadleaf evergreen, broadleaf deciduous, needleleaf evergreen) and a wide latitudinal band (from 44° to 62°N), revealed exceptional fluxes during spring 2007. Gross primary productivity (GPP) of spring 2007 was the maximum recorded in the decade examined for all sites but a Mediterranean evergreen forest (with a +40 to +130 gC m−2 anomaly compared with the decadal mean over the January–May period). Total ecosystem respiration (TER) was also promoted during spring 2007, though less anomalous than GPP (with a +17 to +93 gC m−2 anomaly over 5 months), leading to higher net uptake than the long-term mean at all sites (+12 to +79 gC m−2 anomaly over 5 months). A correlative analysis relating springtime C fluxes to simple phenological indices suggested spring C uptake and temperatures to be related. The CASTANEA process-based model was used to disentangle the seasonality of climatic drivers (incoming radiation, air and soil temperatures) and biological drivers (canopy dynamics, thermal acclimation of photosynthesis to low temperatures) on spring C fluxes along the latitudinal gradient. A sensitivity analysis of model simulations evidenced the roles of (i) an exceptional early budburst combined with elevated air temperature in deciduous sites, and (ii) an early relief of winter thermal acclimation in coniferous sites for the promotion of 2007 spring assimilation.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 13 october 2008; august 2008 and accepted; European forests; functional drivers; net carbon uptake; process-based model; received 30 may 2008; revised version received 30; spring

Changes of the potential distribution area of French Mediterranean forests under global warming - Gaucherel, C.; Guiot, J.; Misson, L. (Biogeosciences, 2008)
This work aims at understanding future spatial and temporal distributions of tree species in the Mediterranean region of France under various climates. We focused on two different species (Pinus Halepensis and Quercus Ilex) and compared their growth under the IPCC-B2 climate scenario in order to quantify signiﬁcant changes between present and future. The inﬂuence of environmental factors such as atmospheric CO2 increase and topography on the tree growth has also been quantiﬁed. We modeled species growth with the help of a processbased model (MAIDEN), previously calibrated over measured ecophysiological and dendrochronological series with a Bayesian scheme. The model was fed with the ARPEGE – MeteoFrance climate model, combined with an explicit increase in CO2 atmospheric concentration. The main output of the model gives the carbon allocation in boles and thus tree production. Our results show that the MAIDEN model is correctly able to simulate pine and oak production in space and time, after detailed calibration and validation stages. Yet, these simulations, mainly based on climate, are indicative and not predictive. The comparison of simulated growth at end of 20th and 21st centuries, show a shift of the pine production optimum from about 650 to 950 m due to 2.5 K temperature increase, while no optimum has been found for oak. With the direct effect of CO2 increase taken into account, both species show a signiﬁcant increase in productivity (+26 and +43% for pine and oak respectively) at the end of the 21st century. While both species have different growth mechanisms, they have a good chance to extend their spatial distribution and their elevation in the Alps during the 21st century under the IPCC-B2 climate scenario. This extension is mainly due to the CO2 fertilization effect.
Keywords: climate modeling (voyant); CO2; Pinus halepensis; Quercus ilex; tree growth